2012
DOI: 10.1017/s0022149x12000193
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the zoonotic potential ofAscaris suumandTrichuris suis: looking to the future from an analysis of the past

Abstract: The two geohelminths, Ascaris lumbricoides and Trichuris trichiura, infect more than a billion people worldwide but are only reported sporadically in the developed part of the world. In contrast, the closely related species A. suum and T. suis in pigs have a truly global distribution, with infected pigs found in most production systems. In areas where pigs and humans live in close proximity or where pig manure is used as fertilizer on vegetables for human consumption, there is a potential risk of cross-infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 78 publications
1
68
0
3
Order By: Relevance
“…Ascaris suum has a high prevalence in pigs in both developed and developing countries, resulting in significant economic penalties for pig farmers [2], [3]. Moreover, A. suum is considered a zoonotic parasite and hybridization between A. suum and A. lumbricoides has been reported [4]. In addition, Ascaris infection also predisposes hosts to co-infection with bacteria and/or protozoa and compromises vaccine efficacy against other pathogens [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ascaris suum has a high prevalence in pigs in both developed and developing countries, resulting in significant economic penalties for pig farmers [2], [3]. Moreover, A. suum is considered a zoonotic parasite and hybridization between A. suum and A. lumbricoides has been reported [4]. In addition, Ascaris infection also predisposes hosts to co-infection with bacteria and/or protozoa and compromises vaccine efficacy against other pathogens [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have been reviewed from different angles to elucidate the taxonomic status of A. lumbricoides and A. suum and their zoonotic potential (323)(324)(325). Several studies using different markers showed zoonotic potential of Ascaris, as humans and pigs were found to share common haplotypes.…”
Section: Ascaris Lumbricoidesmentioning
confidence: 99%
“…1). However, morphological examination alone does not allow eggs, larvae and adult worms to be distinguished between Trichuris trichiura and Trichuris suis (reviewed in [25]). This means that potential cases of crosstransmission between host species cannot be identified using standard parasitological methods.…”
Section: Zoonotic Transmissionmentioning
confidence: 99%